2013
DOI: 10.1556/jba.2.2013.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Relapse in pathological gamblers: A pilot study on the predictive value of different impulsivity measures

Abstract: Backgrounds and aims: Pathological gambling, a common psychiatric disorder, has many similarities with substance use disorders. Relapse, an important element in addictive disorders, however, has seldom been studied in pathological gambling. Hence, in analogy with previous research studies examining the role of self-report and neurocognitive measures on relapse in substance dependent patients, the present pilot study was executed. Methods: Twenty-two pathological gamblers and 31 healthy controls took part in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The association between the inability to tolerate delay and gambling severity, in contrast with past studies (Madden et al, 2009;Miedl et al, 2012;Petry, 2001a;Petry, 2012;Wilde, Goudriaan, Sabbe, Hulstijn, & Dom, 2013) confirms the pattern observed in Alessi and Petry's study (2003). Even if this study does not permit a comprehensive insight into the nature of this relationship, recent research on problem and non-problem gambling adolescents highlights that delay discounting is one of the strongest predictor of gambling problems (Cosenza & Nigro, 2015).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The association between the inability to tolerate delay and gambling severity, in contrast with past studies (Madden et al, 2009;Miedl et al, 2012;Petry, 2001a;Petry, 2012;Wilde, Goudriaan, Sabbe, Hulstijn, & Dom, 2013) confirms the pattern observed in Alessi and Petry's study (2003). Even if this study does not permit a comprehensive insight into the nature of this relationship, recent research on problem and non-problem gambling adolescents highlights that delay discounting is one of the strongest predictor of gambling problems (Cosenza & Nigro, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Although several authors consider delay discounting as a behavioral feature of impulsivity (e.g., Ainslie, 1975;de Wit, 2009), the literature has not clarified the nature of this relationship. Some studies have observed an association between the two constructs (e.g., Alessi & Petry, 2003;Andrade & Petry, 2012;Kräplin et al, 2014;Petry, 2001aPetry, , 2012, whereas other studies have not confirmed this pattern of results (e.g., Madden, Petry, & Johnson, 2009;Wilde, Goudriaan, Sabbe, Hulstijn, & Dom, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, abstinent (e.g., Goudriaan et al, 2005) or non-abstinent (e.g., Power et al, 2012) PG with (e.g., Cavedini et al, 2002) or without co-morbid substance (e.g., Brevers et al, 2012a) abuse seem to display a stubborn preference for disadvantageous deck selection during the IGT, as compared with healthy control participants. Nevertheless, a couple of studies reported non-significant difference between PG and controls on the IGT (Tanabe et al, 2007; Linnet et al, 2011a,b, 2012; De Wilde et al, 2013). This finding could be due to the low sample size of the PG group recruited in these studies (see Table 1).…”
Section: Gambling Disorder and Igt Performancementioning
confidence: 99%
“…The impulsivity domain of the EIQ has shown the most consistent association with gambling severity, with several studies finding that greater EIQ impulsivity scores correlate with a variety of gambling severity measures, and some suggesting it can be used to distinguish problem gamblers from recreational gamblers . Examinations using the BIS and SST in GD have produced mixed results, with certain studies identifying significant clinical associations, whereas others have not . The majority of studies have, however, found that impulsivity is generally greater in GD patients relative to healthy controls and other patients on both the SST and BIS .…”
Section: Introductionmentioning
confidence: 99%